"Doctor, am I an Anglophone trapped in a Francophone body?": An Intersectional Analysis of "Trans-crip-t Time" in Ableist, Cisnormative, Anglonormative Societies. Issue 2 (July 2016) - Baril, Alexandre
Abstract : From a queer, transactivist, intersectional perspective, and adopting a critical genealogy methodology, the article extends the concept of "crip time" to trans people and linguistic minorities. The article suggests a neologism, "trans-crip-t time, " that captures a triple temporality experienced by (1) disabled people ("crip time"); (2) trans people ("trans-crip time"); and (3) minority Francophones and non-Anglophones ("transcript/translation time"). The article aims to stimulate dialogue between these marginalized groups and their associated social movements and fields of study.